Messaging malignancy: Tumour-derived exosomes at the nexus of immune escape, vascular remodelling and metastatic competence - Yildirim Duygu T.; Baki Yildirim A.; Salzet Michel; Bertelli Matteo; Beccari Tommaso; Prakash Satya; Pascucci Luisa; Dundar Munis (The EuroBiotech Journal)
Exosomes, nano-sized extracellular vesicles secreted by all varieties of living cells, have emerged as pivotal mediators of intercellular communication within the tumor microenvironment. While exosomes significantly contribute to tumor progression, metastasis, immune modulation, and resistance to therapy, the mechanisms of cargo selection and clinical translation remain controversial and insufficiently resolved. Recent high-throughput technologies have enabled detailed profiling of exosomal cargo; however, substantial challenges persist in their clinical application due to issues in isolation and standardization. This review systematically dissects these molecular biogenesis controversies, the roles of tumor-derived exosomes in modulating angiogenesis, immune escape, metastasis, and therapy resistance, and critically evaluates barriers hindering their clinical adoption.